PENILAIAN HIGIENE DAN SANITASI PENJUALAN MAKANAN PECEL DAN PEMERIKSAAN BAKTERI Salmonella DI KECAMATAN MEDAN HELVETIA 2015 - gabriella sembiring; surya dharma; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Pecel is a food containing vegetables and using peanut sauce as main composition. During the process, the sellers use hand to make and serve it, instead of wearing gloves. This handmade food tends to be contaminated, mainly by pathogenic microbes which can cause various health risks, such as poisoning, diarrhea, salmonellosis, and other digestic diseases. The method used in the research is descriptive research which is to observe the implementation of hygiene and sanitation of pecel processing.  Laboratory analysis is to determine Salmonella bacteria sold by 35 pecel sellers which are located in Kecamatan Medan Helvetia. The researcher used observation sheet in accordance with the requirements of Hygiene and Sanitation Snacks. The results found that the sellers don’t comply with the principles of food processing comprising storage of food processing comprising selection. As for the principles are not eligible : selection of raw materials of unknown origin, storage of raw materials has not been closed, the processing of food handlers have not qualified, the food storage area is not closed, the transport of food is not closed, and the presentation is done by direct contact with food. As laboratory result do not find Salmonella Bacteria (0/400gr). The researcher suggest that pecel sellers should implement the principles of hygiene and sanitation of food processing in accordance with the regulation. In addition, the government should monitor the food, particularly pecel sellers and provide them with more healthy food instructions. So that the consumers can consume pecel hygienically and safely